Synthesis of mecamylamine analogues - Mangan, David (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
This project was concerned with the synthesis of structural analogues of the neuronal nicotinic acetylcholine receptor (nAChR) antagonist mecamylamine (MA). MA was used clinically as an antihypertensive compound since the 1950s but has more recently been investigated for its therapeutic potential as an anti-addictive and antidepressant compound. Unfortunately MA is viewed as unsuitable for clinical use in this regard due to its non-specific activity at various nAChRs subtypes and it was hoped that by making subtle changes to the molecular structure of MA a novel compound could be found that would display higher selectivity thereby enhancing the therapeutic potential of the parent compound.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.